Pola Komunikasi Kyai Dalam Membangun Budaya Disiplin Santri - Nur Imamah (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the research is to explain and describe the communication patterns used by cottage caretaker in building a culture of santri discipline in Islamic boarding schools. Qualitative research method through case studies. Data collection techniques using interviews, documentation and observation. Data processing techniques: open coding, axial coding, selective coding and theoretical notes. Research results: (1) primary communication pattern: using verbal or non-verbal language with students. (b) secondary communication patterns: using visual or non-visual equipment with students. (c) linear communication pattern: direct face-to-face and non-face-to-face with students. (d) circular communication pattern: two-way communication that occurs continuously between kiai and santri.